Effects of gemfibrozil on the growth, reproduction, and energy stores of Daphnia magna in the presence of varying food concentrations. (February 2018) - Steinkey, Dylan; Lari, Ebrahim; Woodman, Samuel G.; Luong, Kim H.; Wong, Charles S.; Pyle, Greg G.
Abstract: Gemfibrozil, a common lipid regulator, enters aquatic environments through treated municipal wastewater effluent that fails to remove it completely from effluent streams. When exposed to gemfibrozil concentrations of 50, 500, 5, 000, and 50, 000 ng L −1, Daphnia magna showed increased lipid reserves by 14–21% (significant at 500 ng L −1 ), increased length by 9–13% (significant at 50 ng L −1 ), increased mass by 6–13% (significant at 50 ng L −1 ) and increased neonate production by 57–74% (significant at 50 ng L −1 ). Gemfibrozil-exposed Daphnia held under conditions where food availability was low, grew and reproduced as well as those in the control. Taken together, these results suggest that gemfibrozil exposure within environmentally relevant concentration ranges is not toxic to Daphnia magna but has the potential to be beneficial to the species under these conditions. Highlights: D. magna exposed to gemfibrozil grew larger and produced more neonates. Exposed D. magna increased their lipid stores over 21 days. Exposed D. magna did not differ from controls in experiments with reduced feeding.